Preparation method of ternary two-dimensional material macroscopic assembled membrane

The preparation of macroscopic assembled films of Ta2NiSe5 or Ta2NiS5 through liquid phase interpolation and electrochemical peeling technology, solving the stability and performance problems of two-dimensional materials in the application of IR photodetectors in the prior art, and achieving high-performance infrared light detection and imaging effects.

CN119900089AInactive Publication Date: 2025-04-29WENZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510381511.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing IR photodetectors rely on three-dimensional crystal structures, and have problems with volume-related thermal noise, pixel size limitations, and difficulties in miniaturization. Two-dimensional materials also have challenges in terms of low photoresponsiveness, poor material preparation stability, poor environmental stability, and difficult to make micro-sheet material devices.

Method used

The sheets of Ta2NiSe5 or Ta2NiS5 are made into macroscopic assembled membranes by liquid intercalation method, and high-quality macroscopic assembled membranes are formed by electrochemical peeling and suction filtration technology, and a complete membrane material is obtained by lyophilization annealing.

Benefits of technology

The high-performance macroscopic assembled film preparation of ternary two-dimensional materials is achieved, with the advantages of high flux, low processing temperature and good stability. It can better utilize the properties of each layer of material, and promote its application in infrared light detection and imaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900089A_ABST
    Figure CN119900089A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a ternary two-dimensional material macroscopic assembly film. The preparation method comprises the following steps: 1) synthesizing a crystal material Ta2NiSe5 or Ta2NiSe5; 2) performing electrochemical stripping on the crystal material; and 3) carrying out suction filtration on the stripped material, and then transferring the macroscopic assembled membrane subjected to suction filtration to a silicon wafer for freeze-drying and annealing to obtain the complete macroscopic assembled membrane. The macroscopic assembled membrane is prepared through electrochemical stripping and liquid nitrogen transfer. The two-dimensional material crystal is stripped and scattered, the material is multiplied and then combined to form a macroscopic tissue membrane, the advantages of high flux, low processing temperature, good stability and the like are achieved, the properties of each layer of material can be better utilized, and application of the ternary two-dimensional material in the aspects of infrared light detection and imaging of a high-performance thin film transistor is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material synthesis, and in particular relates to a method for preparing a macroscopic assembly film of a ternary two-dimensional material. Background Art

[0002] Infrared (IR) photodetectors are detectors that can detect light waves in the wavelength range of 0.8–30 µm. They are widely used in medical imaging, military detection, optical communications, security monitoring, remote sensing, gas identification, consumer electronics, etc. To date, commercial IR photodetectors generally rely on compound semiconductors with three-dimensional crystal structures. However, these mature IR photodetection technologies still have shortcomings, such as volume-related thermal noise, pixel size limitations, and challenges such as miniaturization difficulties.

[0003] Compared with bulk compound semiconductors used in IR photodetectors, two-dimensional materials have the following advantages: simple manufacturing process, strong light-matter interaction per unit volume, excellent heterogeneous integration capability, and can well achieve complementary, fusion and integration with silicon. However, two-dimensional materials still have key problems such as weak light absorption, easy transformation of conventional two-dimensional semiconductor multilayer materials into indirect band gap, low light response, poor material preparation stability, poor environmental stability, and difficulty in making devices with tiny sheet materials, which hinder their practical application.

[0004] Combining the excellent properties of Ta2NiSe5 and Ta2NiS5, the key to solving the above problems is to use the liquid phase intercalation method to make the dissociated thin sheets into macroscopic assembled films. The method of peeling and breaking up the two-dimensional material crystals and then merging and gathering them to form a macroscopic assembled film is a good way to expand two-dimensional materials, which can well expand and utilize the unique properties of two-dimensional materials; compared with the common chemical vapor deposition (CVD) method in the industry, it has the advantages of high flux, low processing temperature, and good stability. In addition, this preparation method can very well reflect the uniqueness of two-dimensional materials, break the van der Waals effect between the layers of two-dimensional materials, multiply the materials, and expand to form a macroscopic tissue film, which can better utilize the properties of each layer of materials; conventional bulk lattice materials cannot do this. Theoretical analysis results show that ternary Ta2NiSe5, Ta2NiS5 and other materials have direct band gaps from single layers to multiple layers. And after these materials are made into macroscopic tissue films, combined with the device preparation and integration process, infrared light detection can be carried out, and the membrane materials can be integrated into infrared detection chips, which is expected to be used for infrared imaging applications. At present, there are no reports on the production of macroscopic assembled films with ternary materials and the excellent properties they show. Summary of the invention

[0005] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a macroscopic assembly film of ternary two-dimensional materials.

[0006] The present invention is achieved through the following technical solutions: A method for preparing a macroscopic assembly film of a ternary two-dimensional material, the method comprising the following steps: 1) Synthesis of high-quality crystalline materials, wherein the crystalline materials include Ta2NiSe5 single crystals or Ta2NiS5 single crystals; 2) using an electrolytic device to electrochemically exfoliate the crystalline material obtained in step 1); 3) The material stripped in step 2) is filtered, and then the filtered macro-assembly membrane is transferred to a silicon wafer for freeze-drying and annealing to obtain a complete macro-assembly membrane.

[0007] Furthermore, in step 1), Ta2NiSe5 single crystal synthesis adopts tantalum powder, nickel iodide and selenium powder to be weighed and mixed in a stoichiometric ratio of 2:1:5, and iodine element is used as a transport agent. Specifically, the above raw materials are vacuum sealed in a quartz tube, one end of the tube is slowly heated to 850°C, and the other end is heated and maintained at 800°C. After 10 days of growth, strip-shaped shiny crystals are obtained.

[0008] Furthermore, in step 1), Ta2NiS5 single crystal synthesis is carried out by weighing and mixing tantalum powder, nickel iodide and sulfur powder in a stoichiometric ratio of 2:1:5, and using iodine as a transport agent. Specifically, the above raw materials are vacuum sealed in a quartz tube, one end of the tube is slowly heated to 950°C, and the other end is heated and maintained at 870°C. After 10 days of growth, strip-shaped shiny crystals are obtained.

[0009] Furthermore, in step 2), an organic ammonium salt is selected as the electrolyte, and the electrolysis device uses a DC regulated power supply for electrolysis. During electrolysis, the negative electrode uses a platinum electrode clamp to first clamp the material. Specifically, the material is first clamped with nickel foam, and then the nickel foam is clamped with a platinum electrode clamp to prevent the material from falling. The other platinum electrode serves as the positive electrode.

[0010] Furthermore, the organic ammonium salt is tetramethylammonium chloride, and the electrolyte is an aqueous solution of tetramethylammonium chloride with a concentration of 0.05 mol / L.

[0011] Furthermore, the power supply adopts a steady current mode, and the current is stabilized at 0.1 A.

[0012] Furthermore, in step 3), the stripped material is centrifugally washed, washed three times with water, and then prepared into a solution for suction filtration, and the filter membrane is an anodized aluminum membrane.

[0013] Furthermore, in step 3), the filter membrane transfer process requires first steaming a layer of camphor on the filtered material, then immersing it in liquid nitrogen for 20 seconds and then clamping it up, repeating this three times and then placing it in 5% dilute phosphoric acid. The macro-assembled membrane will be separated from the anodized aluminum membrane, and then freeze-dried and annealed to obtain a complete macro-assembled membrane.

[0014] The method of the present invention is to realize the controllable preparation, electrochemical stripping, and preparation of macroscopic assembly films of ternary van der Waals materials Ta2NiSe5 or Ta2NiS5 through chemical vapor transport (CVT). The macroscopic tissue film formed by stripping and breaking up the two-dimensional material crystals and doubling the materials has the advantages of high flux, low processing temperature, good stability, etc., and can better utilize the properties of each layer of material, promote the application of ternary two-dimensional materials in high-performance thin-film transistor infrared light detection and imaging, and make reserves for advanced infrared photoelectric imaging technology based on Ta2NiSe5 or Ta2NiS5 macroscopic assembly films. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 A schematic diagram of a device for synthesizing CVT materials; Figure 2 Optical image of Ta2NiSe5 synthesized by CVT; Figure 3 This is an optical image of Ta2NiSe5 after stripping; Figure 4 This is the AFM image of Ta2NiSe5 after peeling; Figure 5 This is an optical picture of the Ta2NiSe5 macroscopic assembled film after filtration; Figure 6 Optical image of Ta2NiSe5 macro-assembly film after transfer annealing; Figure 7 Raman spectra of Ta2NiSe5 macro-assembled films after transfer annealing; Figure 8 X-ray diffraction spectrum of Ta2NiSe5 macro-assembly film after transfer annealing; Fig. 9 Optical image of Ta2NiS5 synthesized by CVT; Fig.10 This is an optical image of Ta2NiS5 after stripping; Fig.11 This is a scanning atomic force microscope (AFM) image of Ta2NiS5 after exfoliation; Fig.12 This is an optical picture of the Ta2NiS5 macro-assembly film after filtration; Fig.13 Optical image of Ta2NiS5 macro-assembly film after transfer annealing; Fig.14 Raman spectra of Ta2NiS5 macro-assembled films after transfer annealing; Fig.15 X-ray diffraction spectrum of Ta2NiS5 macro-assembled film after transfer annealing. DETAILED DESCRIPTION

[0016] The present invention is further described below in conjunction with specific embodiments and accompanying drawings to facilitate a better understanding of the present technical solution.

[0017] Example 1

[0018] To synthesize high-quality Ta2NiSe5 single crystals, tantalum powder, nickel iodide and selenium powder were weighed and mixed in a stoichiometric ratio of 2:1:5, and iodine was used as a transport agent. The above chemicals were vacuum sealed in a quartz tube, one end of the tube was slowly heated to 850℃, and the other end of the tube was heated and maintained at 800℃. After 10 days of growth, strip-shaped shiny crystals were obtained. The crystal material was electrochemically stripped, and an organic ammonium salt (tetramethylammonium chloride) was selected as the electrolyte. 0.548 g of tetramethylammonium chloride was weighed and dissolved in 100 ml of ultrapure water to prepare a 0.05 mol / L electrolyte. The electrolysis device used a DC regulated power supply for electrolysis. During electrolysis, the two electrodes were clamped with platinum points, and nickel foam assisted in clamping the material in 0.05 mol / L tetramethylammonium chloride. The negative electrode used a platinum electrode clamp to clamp the material (first clamp the material with nickel foam, and then clamp the nickel foam with a platinum electrode clamp) to prevent the material from falling, and the other platinum electrode was used as the positive electrode. The power supply adopts the steady current mode, and the current is stable at 0.1 A. The stripped material is centrifuged and washed, washed with water three times, and then prepared into a solution for filtration. The filter membrane uses an anodic aluminum oxide (AAO) membrane. The filter membrane transfer process requires first steaming a layer of camphor on the filtered material, then immersing it in liquid nitrogen for 20 seconds and then clamping it up. After repeating three times, it is placed in 5% dilute phosphoric acid, and the macro-assembled membrane will be separated from the AAO membrane. Then freeze-dried and annealed to obtain a complete macro-assembled membrane.

[0019] like Figure 1 The figure shows a schematic diagram of a device for synthesizing CVT materials. The synthesized raw materials are placed at the high temperature end, and crystals are formed at the low temperature end.

[0020] like Figure 2 The figure shows the morphology of Ta2NiSe5 synthesized in this embodiment. The optical image shows that the sample is a needle-shaped crystal with a length of about 1 cm.

[0021] like Figure 3 As shown, this is an optical image of Ta2NiSe5 after electrochemical stripping, with a lateral size of up to tens of microns.

[0022] like Figure 4 As shown, it is an AFM image of Ta2NiSe5 after electrochemical stripping. The thickness of the sample after stripping is about 30 nm.

[0023] like Figure 5 As shown, it is an optical picture of the macroscopic assembled membrane after filtration. After filtration, a continuous and complete macroscopic assembled membrane is obtained.

[0024] like Figure 6 Shown is an optical image of the macroscopic assembled film after transfer annealing.

[0025] like Figure 7 As shown, it is the Raman spectrum of the macroscopic assembled film after transfer annealing, which is consistent with the Raman peak position of Ta2NiSe5, proving that the Ta2NiSe5 macroscopic assembled film was successfully prepared.

[0026] like Figure 8 As shown, it is the X-ray diffraction spectrum of the macroscopic assembled film after transfer annealing, which is consistent with the XRD in the literature, further proving that the Ta2NiSe5 macroscopic assembled film was successfully prepared.

[0027] Example 2

[0028] To synthesize high-quality Ta2NiS5 single crystals, tantalum powder, nickel iodide and sulfur powder were weighed and mixed in a stoichiometric ratio of 2:1:5, and iodine was used as a transport agent. The above-mentioned chemicals were vacuum sealed in a quartz tube, one end of the tube was slowly heated to 950°C, and the other end was heated to 870°C. After 10 days of growth, strip-shaped shiny crystals were obtained. The crystal material was electrochemically stripped, and an organic ammonium salt (tetramethylammonium chloride) was selected as the electrolyte. 0.548 g of tetramethylammonium chloride was weighed and dissolved in 100 ml of ultrapure water to prepare an electrolyte of 0.05 mol / L. The electrolysis device used a DC regulated power supply for electrolysis. During electrolysis, the negative electrode used a platinum electrode clamp to clamp the material (first clamp the material with nickel foam, and then clamp the nickel foam with a platinum electrode clamp) to prevent the material from falling, and the other platinum electrode was used as the positive electrode. The power supply adopts a steady current mode, and the current is stable at 0.1 A. The stripped material was centrifuged and washed three times with water to prepare a solution for suction filtration, and the filter membrane was AAO membrane. The filter membrane transfer process required first steaming a layer of camphor on the filtered material, then immersing it in liquid nitrogen for 20 seconds and then clamping it up. After repeating three times, it was placed in 5% dilute phosphoric acid, and the macro-assembly membrane would be separated from the AAO membrane. Then freeze-dried and annealed to obtain a complete macro-assembly membrane.

[0029] like Fig. 9 As shown, it is the morphology of Ta2NiS5 synthesized in this embodiment. The optical image shows that the sample is a needle-shaped crystal with a length of about 1 cm.

[0030] like Fig.10 As shown, this is an optical image of Ta2NiS5 after electrochemical stripping, with a lateral size of up to tens of microns.

[0031] like Fig.11 As shown, it is an AFM image of Ta2NiS5 after electrochemical stripping. The thickness of the sample after stripping is about 32 nm.

[0032] like Fig.12As shown, it is an optical picture of the macroscopic assembled membrane after filtration. After filtration, a continuous and complete macroscopic assembled membrane is obtained.

[0033] like Fig.13 Shown is an optical image of the macroscopic assembled film after transfer annealing.

[0034] like Fig.14 As shown, it is the Raman spectrum of the macroscopic assembled film after transfer annealing, which is consistent with the Raman peak position of Ta2NiS5, proving that the Ta2NiS5 macroscopic assembled film was successfully prepared.

[0035] like Fig.15 As shown, it is the X-ray diffraction spectrum of the macroscopic assembled film after transfer annealing, which is consistent with the XRD in the literature, further proving that the Ta2NiS5 macroscopic assembled film was successfully prepared.

Claims

1. A method for preparing a macroscopic assembly film of a ternary two-dimensional material, characterized in that: The preparation method comprises the following steps: 1) Synthesis of high-quality crystalline materials, wherein the crystalline materials include Ta2NiSe5 single crystals or Ta2NiS5 single crystals; 2) using an electrolytic device to electrochemically exfoliate the crystalline material obtained in step 1); 3) The material stripped in step 2) is filtered, and then the filtered macro-assembly membrane is transferred to a silicon wafer for freeze-drying and annealing to obtain a complete macro-assembly membrane.

2. The method for preparing a macroscopic assembly film of a ternary two-dimensional material according to claim 1, characterized in that In step 1), Ta2NiSe5 single crystal synthesis uses tantalum powder, nickel iodide and selenium powder weighed and mixed in a stoichiometric ratio of 2:1:5, and iodine is used as a transport agent. Specifically, the above raw materials are vacuum sealed in a quartz tube, one end of the tube is slowly heated to 850°C, and the other end is heated and maintained at 800°C. After 10 days of growth, strip-shaped shiny crystals are obtained.

3. The method for preparing a macroscopic assembly film of a ternary two-dimensional material according to claim 1, characterized in that In step 1), Ta2NiS5 single crystal synthesis is carried out by weighing and mixing tantalum powder, nickel iodide and sulfur powder in a stoichiometric ratio of 2:1:5, and iodine is used as a transport agent. Specifically, the above raw materials are vacuum sealed in a quartz tube, one end of the tube is slowly heated to 950°C, and the other end is heated and maintained at 870°C. After 10 days of growth, a strip-shaped shiny crystal is obtained.

4. The method for preparing a macroscopic assembly film of a ternary two-dimensional material according to claim 1, characterized in that In step 2), an organic ammonium salt is selected as the electrolyte, and the electrolysis device uses a DC regulated power supply for electrolysis. During electrolysis, the negative electrode uses a platinum electrode clamp to clamp the material first to prevent the material from falling, and the other platinum electrode is used as the positive electrode.

5. The method for preparing a macroscopic assembly film of a ternary two-dimensional material according to claim 4, characterized in that: The organic ammonium salt is tetramethylammonium chloride, and the electrolyte is an aqueous solution of tetramethylammonium chloride with a concentration of 0.05 mol / L.

6. The method for preparing a macroscopic assembly film of a ternary two-dimensional material according to claim 4, characterized in that: The power supply adopts the steady current mode and the current is stable at 0.1 A.

7. The method for preparing a macroscopic assembly film of a ternary two-dimensional material according to claim 1, characterized in that In step 3), the stripped material is centrifugally washed by suction filtration and washed three times with water to prepare a solution for suction filtration, and the filter membrane is an anodized aluminum membrane.

8. The method for preparing a macroscopic assembly film of a ternary two-dimensional material according to claim 1, characterized in that In step 3), the filter membrane transfer process requires first steaming a layer of camphor on the filtered material, then immersing it in liquid nitrogen for 20 seconds and then clamping it up. After repeating this three times, it is placed in 5% dilute phosphoric acid. The macro-assembled membrane will be separated from the anodized aluminum membrane, and then freeze-dried and annealed to obtain a complete macro-assembled membrane.

Citation Information

Patent Citations

  • Method for stripping ferric thiophosphate crystal synchronously doped monatomic by electrochemical assistance

    CN113880060A

  • Broadband photoelectric detector based on novel two-dimensional topological material and preparation method thereof

    CN116314387A

  • Application of independent self-supporting graphene film as heavy ion accelerator carbon stripping film

    CN117945396A